The Orchestrator’s Dilemma: How Ericsson Strategically Recombined Resource Commitments and Signaling Tactics to Outmaneuver WiMAX - Khanagha, Saeed; Ansari, Shahzad (Shaz); Rindova, Violina; Ozalp, Hakan (Journal of Management, 2025)
Orchestrators shape ecosystem development by aligning diverse participants while advancing their own competitive agendas. This alignment becomes fragile when a new entrant offers an alternative value proposition that appeals to ecosystem participants but threatens an orchestrator’s position. Whereas prior research highlights the success of new entrants, less is known about how an orchestrator defends its competitive interests and position while addressing expectations of cooperation from ecosystem participants, which we call the “orchestrator’s dilemma.” We investigate these dynamics through a longitudinal study of Ericsson’s responses as Intel attempted to promote WiMAX as an alternative to LTE, Ericsson’s fourth-generation mobile technology. Our analysis shows how Ericsson recombined its substantive resource commitments and signaling tactics to develop three distinct strategic responses—avoiding competition, covert competition, and overt competition—as ecosystem support for the new entrant’s value proposition changed over time. We show how an orchestrator can defend its position against disruptive entrants by decoupling signaling tactics from substantive resource commitments to influence ecosystem dynamics. We contribute by theorizing these dynamic strategic responses as a way to overcome the orchestrator’s dilemma and by highlighting the social aspects of ecosystem alignment and its fragility.